Embodied agents in E-learning environments: An exploratory case study - Mahmood, Ahmad Kamil (2006)
There is increasing interest in embodied agents (or avatars) and the effects on human cognition and motivation. Specifically there is an increasing interest in the use of embodied agents in e-learning environments. However, empirical investigations into the use of embodied agents in online education are limited. Our aim is to provide a framework for the development and evaluation of embodied agents in e-learning environments. The framework is derived from an indepth interpretive case study. This framework is useful for practitioners and researchers into courseware and embodied agent development, providing guidelines for embodied agent design and implementation in e-learning environments. There are a number of key findings, perhaps the most challenging being the dichotomous relationship that emerges between lecturer and student perception of the degree of autonomy that can be afforded to embodied agents. The research findings suggest that educators favour highly controlled embodied agents with limited autonomy while students are looking for more autonomous embodied agents that are highly personalised and can act as an informal interface between themselves and the lecturer.